Tanshinone Ameliorates Glucocorticoid-Induced Bone Loss via Activation of AKT1 Signaling Pathway - Wang, Yanjun; Liu, Lin; Qu, Zechao; Wang, Dong; Huang, Wangli; Kong, Lingbo; Yan, Liang (Frontiers in Cell and Developmental Biology, 2022)
Purpose: Osteoporosis is a common disorder in postmenopausal women and the elderly, becoming a worldwide public health problem. Osteoporosis can cause joint pain, fragility fractures, and other symptoms, which seriously impair the patients’ daily life. Currently, there is no gold-standard drug that can completely cure osteoporosis. Tanshinone is a traditional Chinese medicine with multiple biological activities. It may have a protective effect on osteoporosis. However, the molecular mechanism of how tanshinone improves osteoporosis remains unclear. The objective of our study is to explore the underlying mechanism. Methods: The common KEGG pathways of tanshinone-targeted genes and osteoporosis were studied by us using bioinformatics analysis. The bioinformatics analysis results were further validated by in vitro and in vivo experiments. Results: 21 common KEGG pathways were identified between osteoporosis and tanshinone-targeted genes. It was further found that tanshinone could induce the AKT1 expression, promote the MSCs proliferation, and suppress the apoptosis of MSCs. Conclusion: Taken together, we conclude that tanshinone can alleviate osteoporosis which is potentially mediated through modulating PI3K-Akt signaling pathway. Tanshinone could be a promising treatment for osteoporosis.